Multiple fractures in infants who have Ehlers-Danlos/hypermobility syndrome and or vitamin D deficiency: A case series of 72 infants whose parents were accused of child abuse and neglect. Issue 1 (1st January 2017) - Holick, M. F.; Hossein-Nezhad, A.; Tabatabaei, F.
ABSTRACT: Objective : To increase the level of awareness that Ehlers-Danlos/hypermobility syndrome (EDS) and vitamin D deficiency are associated with infantile fragility fractures and radiologic features that may be mistakenly reported to be caused by non-accidental trauma due to Child Abuse and Neglect (CAN). Patients and Methods : We constructed a case series, the largest to date, of infants with EDS who were vitamin D sufficient, insufficient and deficient and infants without EDS but with documented vitamin D deficiency and radiologic evidence of rickets who presented with multiple fractures originally diagnosed as being non-accidental and caused by child abuse. These infants were referred to the outpatient Bone Health Care Clinic at Boston University Medical Campus over a 6-year (2010–2015) period. We also present 6 index cases in which the court concluded that there was no convincing evidence of child abuse and the infants were returned to their parents. Institutional Review Board (IRB) approval was obtained. Results : We present 72 cases of infants with multiple fractures diagnosed to be caused by non-accidental trauma. All infants were younger than one year of age. Among them, 93%(67) had clinical evidence of EDS and/or a family history with a confirmed clinical diagnosis of at least one parent having EDS and the other 7%(5) without evidence of EDS had vitamin D deficiency/infantile rickets. Three of the EDS infants were diagnosed as osteogenesis imperfecta (OI)/EDS overlap syndrome. The most common fractures noted at diagnosis were ribs and extremity fractures (including classic metaphyseal lesions). Serum levels of 25-hydroxyvitamin D [25(OH)D] were reported in 48 infants (18.0 ± 8.5 ng/ml) and in 30 mothers (21.3 ± 11.7 ng/ml). Sixty-three percent (27) of the EDS infants who had their serum 25(OH)D measured were vitamin D deficient 25(OH)D<20 ng/ml and 5 were vitamin D sufficient 25(OH)D>30 ng/ml. The mean serum level for infants with vitamin D deficiency/rickets was (10.2 ± 3.0 ng/ml) Conclusion : EDS, OI/EDS and vitamin D deficiency/infantile rickets are associated with fragility fractures in infants that can be misinterpreted as caused by non-accidental trauma due to child abuse.